PENERAPAN MEDIA PEMBELAJARAN BERBASIS ANIMASI MULTIMEDIA UNTUK MENGENALKAN MATA UANG KEPADA ANAK - Afit Syahputra; M. Sani Hafiz Rusydi, Afif Imran Prasetyo, Muhammad Fajar, Apdi Lubis (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Introducing currency is a crucial aspect of financial education, especially for children. However, traditional methods often lack appeal for them. Hence, this research aims to implement multimedia animation-based currency introduction learning media for children. The method involves developing engaging and easy-to- understand multimedia animation content for children. Data collection is done through direct observation of children's reactions and understanding levels towards the implemented learning media. Additionally, assessment is conducted on children's ability to identify and understand currency values after using this learning media. The research findings indicate that implementing multimedia animation- based currency introduction learning media can significantly enhance children's interest and understanding of currency. Children demonstrate high levels of engagement during the learning process, and their ability to identify and understand currency values improves significantly after using this learning media.